Rules of Action in Policy Networks: Study at the Environment Service of Sukabumi City - Ahmad Hidayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Each agency has a work culture that functions to form rules or guidelines in thinking and acting in achieving the goals set. The purpose of this article is to find out the role of DLHK in the perspective of habits or rules of the game in the interactions that govern exchanges in a network. This stems from the perception of the roles, attitudes, interests, and social and educational backgrounds of the actors involved. Based on one of the dimensions of the Policy Network, namely the rules of action, using phenomenological qualitative research methods. This study draws the conclusion that the DLH Sukabumi City in carrying out the rules of action based on the IKLH which includes 3 components, namely the Air Quality Index, Water and Land Cover, these three are factors for finding solutions to complaints and public submissions.